SURVEI KONDISI FISIK ATLET DAYUNG PERAHU NAGA PUTRI DI KLUB BADJOEL SURABAYA - DEBRITO DANANG AJI WIC, YOHANES Debrito (Jurnal Prestasi Olahraga, 2013)
The components of physical conditions which are needed by the paddlers are endurance, flexibility and strength. Endurance which is needed by a paddler are general endurance, arm muscle and abdominal muscle local endurance. The purpose of this research is to know about female athletes? physical condition of dragon boat in Badjoel club Surabaya. This research used quantitative non experiment with descriptive quantitative model approach. The technique which is used in this research by using five tests of physical condition, they are: the leg muscle strength test, sit and reach test, abdominal muscle endurance test, muscle endurance arm test and bleep test. The researcher obtained his data by conducting a simple statistical analysis technique which is used to find mean, standard deviation and percentage. The results of this research are average of leg muscle strength is 83.46 with less criteria, back muscles flexibility has average 15.24 with less criteria, stomach muscle strength has average of 44.13 with reasonable criteria, while arm muscle endurance has an average of 45.13 with reasonable criteria and VO? max level has average of 33.12 with reasonable criteria. We can conclude that female athletes? physical condition of dragon boat in Badjoel club Surabaya is still less from the maximum target. Keywords              : Female Athlete, Physical Condition, Dragon Boat